Análise da sustentabilidade de bacias hidrográficas do estado do Ceará - Soares, Andressa Bezerra (2007)
Environmental issues and quality of life of the current and future generations are recurrent concerns of the society. The academic and enterprise entities have developed studies to guarantee the sustainable development, conceived as compatible economic growth with the preservation of the environment and the quality of life through a long time. In this context, the water became prominent as an essential natural resources for the humanity whose scarcity or inappropriate for some uses is presented as a serious problem to be faced by the society. Thus, it suggests to verify the sustainability of the catchments, Alto Jaguaribe, Curu and Metropolitana, located in the state of the Ceará, from parameters that identify its economic, social and ambient characteristics and of the levels of answers of the society by the public politics. The analysis is based on a quantitative boarding, using the called DPSIR framework (Driving Force, Pressure, State, Impact, Response), defined on the basis of the cause and effect relationships, where the three first components (Driving Force, Pressure, State) are the cause of the problem, the fourth (Impact) is the problem in itself and the fifth (Response) is the society´s answers to solve it. The empirical evaluation was maked with the use of software MULINO mDSS, developed by the European Community. With the modeling using the software mDSS can done the sustainable chart that allows to visualize the standard of sustainability of the catchments. The analysis follows two criterias: a static, comparing the results of the three catchments of the sample, for the year of 2000; another one, static- comparative , that compares the alteration of the sustainability between 2000 and 2010, as scene of projected pointers for this last year. In the static analysis of 2000, the Catchment Metropolitan presented the greater scores of sustainability, however the Catchment Alto Jaguaribe is more balanced in relation of the three dimensions of sustainability. Already, in the static-comparative analysis, all the three catchments had presented better scores and balances in 2010. Concludes that the used of DPSIR framework and the computational program can subsidize the analysis of the sustainability of catchments in its three dimensions.